Embedding Impact in Engaged Research: Developing Socially Useful Knowledge through Dialogical Sensemaking. (January 2017) - Cunliffe, Ann L.; Scaratti, Giuseppe
Abstract : This paper explores how we can embed impact in research to generate socially useful knowledge. Our contribution lies in proposing a form of engaged research that draws upon situated knowledge and encompasses dialogical sensemaking as a way of making experience sensible in collaborative researcher−practitioner conversations. We draw attention to the intricacies of doing socially useful research and illustrate how five conversational resources can be used within dialogical sensemaking through an example of a research project in which impact and relevance were embedded and where researchers and practitioners worked together to resolve an important social and organizational issue.